Efektifitas Slow Stroke Back Massage Terhadap Lansia Dengan Hipertensi - Andi Jayawardhana (2018)
ABSTRACT This study aims to determine the effectiveness of slow stroke back massage against elderly with hypertension in UPTD Griya Werdha Jambangan Surabaya. The research design was Quasy Experiment with Non Equivalent Control Design wich was used by 30 respondents with Random Sampling Technique, devided into 2 groups, 15 control group respondents and 15 respondent of treatment group taken from the inclusion criteria. Data in this study were taken using blood pressure observation sheet. After done tabulation of data, then tested statistic by using Paired t-Test with significance level 0,05. Statistical test result showed that there was significant effect of slow stroke back massage on MAP decrease in elderly with hypertension, with significant value (2-tailed) 0.000 (p < 0,05).